2015
DOI: 10.3343/alm.2015.35.6.624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Anyplex BRAF V600E Real-Time Detection Assay Using Dual-Priming Oligonucleotide Technology in Fine-Needle Aspirates of Thyroid Nodules

Abstract: BackgroundSeveral molecular assays have been developed to detect the BRAF V600E mutation in fine needle aspirates (FNAs) for the diagnosis of papillary thyroid cancer. Using a multiplex PCR technique, we evaluated the Anyplex BRAF V600E Real-time Detection (Anyplex) assay and compared its efficacy with that of the Seeplex BRAF V600E ACE Detection (Seeplex) method.MethodsWe tested 258 consecutive FNA specimens using the Seeplex and Anyplex assays. Any conflicting results between the two assays were confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In contrast, the risk of malignancy of indeterminate thyroid nodules, such as atypia of undetermined significance/follicular lesion of undermined significance (AUS/FLUS) and follicular neoplasm/suspicious for follicular neoplasm (FN/SFN), is 11%-23% and 20%-29%, respectively [11]. Therefore, additional molecular assays are used to investigate these indeterminate nodules [10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the risk of malignancy of indeterminate thyroid nodules, such as atypia of undetermined significance/follicular lesion of undermined significance (AUS/FLUS) and follicular neoplasm/suspicious for follicular neoplasm (FN/SFN), is 11%-23% and 20%-29%, respectively [11]. Therefore, additional molecular assays are used to investigate these indeterminate nodules [10,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several molecular assays have been developed to detect the B-Raf proto-oncogene (BRAF) V600E mutation in fine-needle aspirates for the diagnosis of papillary thyroid cancer (PTC). 13 Musholt et al 14 considered that mutations of RET/PTC, RAS, and PAX8/peroxisome proliferator-activated receptor ␥ (PPAR␥) were predominantly associated with thyroid malignancy with varying frequency and had less impact on the clinical management. However, in the study of Song et al, 15 BRAF mutations were the most common ones observed in PTCs, followed by RET/PTC rearrangements and RAS mutations, while follicular thyroid cancers were more likely to have RAS mutations or PAX8/PPAR␥ rearrangements.…”
mentioning
confidence: 99%